Phase changes during the drying of calcium aluminate cement bond castables – the influence of curing and drying conditions - Köhler, Andreas; Neubauer, Jürgen; Götz-Neunhoeffer, Friedlinde (Cement, 2022)
This study presents the influence of different curing temperatures and the availability of unbound H2O on the phase changes during the drying process of a simplified calcium aluminate cement bond castable. A mixture of CAC and alumina was hydrated for 48 h at 5, 23 and 40 °C, which represents different working conditions during casting. After the curing process, these samples were heated up to 180 °C, and in some of them, the remaining unbound H2O had been removed by vacuum drying beforehand. The quantitative phase composition was determined by QXRD. Thermogravimetric analysis and gravimetric measurements were also used to characterize the differently cured samples. While the mineral phases in the samples cured at 40 °C were barely affected by the heating process in the investigated temperature range, the initial conditions before the drying of the samples cured at 5 and 23 °C strongly affected the final phase composition.
Keywords: Curing; Drying; Hydration; Temperature; X-ray diffraction; Calcium aluminate cement; Refractory cement